Pengaruh Durasi Penggunaan Gawai terhadap Keluhan Nyeri Leher Mahasiswa Jurusan Fisioterapi Poltekkes Kemenkes Surakarta - Wardani, Ulfah Eka; Kusumawati, Yoni Rustiana; Sari, Kernia Elviana; Utomo, Budi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Gadgets are modern communication tools designed with advanced technology to facilitate communication. Prolonged use of gadgets can lead to excessive load on the cervical spine, resulting in neck pain. Objectives: This study aims to determine the effect of gadget usage duration on neck pain complaints among students of the Physiotherapy Department at Poltekkes Kemenkes Surakarta. Methods: This research employed a comparative analytical design with a cross-sectional approach. A total of 212 active students from the Physiotherapy Department at Poltekkes Kemenkes Surakarta were selected through an online questionnaire. The variables examined included daily gadget usage duration and the level of neck pain, measured using the Numeric Rating Scale (NRS). Data were analyzed using the Chi-square test. Results: The findings showed that the majority of respondents used gadgets for more than 6 hours per day (117 respondents), and most reported mild neck pain (138 respondents). However, the Chi-square test produced a p-value of 0.941 (p > 0.05), indicating that there was no significant relationship between gadget usage duration and neck pain complaints among the physiotherapy students. Although neck pain complaints were more commonly found among respondents with longer gadget use duration, the relationship was not statistically proven. Conclusion: Based on the results, it can be concluded that the duration of gadget use does not affect the frequency level of neck pain complaints among students of the Physiotherapy Department at Poltekkes Kemenkes Surakarta. Keywords : Gadget, Usage duration, Neck pain, Students, Physiotherapy